(untitled) (Research, Society and Development, 2020)
Coronavirus, also known as COVID-19, is a disease that has arrived in the world bringing a new routine and new perspectives in health care for the population, once pretty little is known about it. In addition, we know that it has high transmissibility, and a very rapid spread among people, leading to a large number of hospitalizations and deaths.This article reflects on the changes in the flow, and the processing protocol of ventilatory materials within the Material and Sterilization Center, especially with regard to the care of staff in these sectors; also the use of Personal Protective Equipment, and the training carried out to guarantee the quality of the service provided and the safety of the professionals. As a method, the arguments are based on the resolutions, determinations, and protocols of the National Health Surveillance Agency which works in the construction of norms and laws that support the good practices in health services. We conclude that it is essential that the frontline teams be well trained, and have well-defined protocols for daily activities.